Literature Review: Misconceptions of 7th Grade Students on the Concepts of Direct and Inverse Proportion - Selpiana Selpiana; Usman Mulbar (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
Direct and inverse proportionality are important concepts in junior high school mathematics, yet seventh-grade students often experience misconceptions regarding these topics. This study aims to identify the types of misconceptions, their underlying causes, and effective instructional strategies to address them. The method used is a literature review of 22 articles from credible sources, including Sinta-indexed journals, Scopus, International journals, and Google Scholar. The analysis results indicate that student misconceptions mostly stem from underdeveloped conceptual understanding, limited mathematical reasoning skills, and low metacognitive abilities. The difficulties include errors in distinguishing between direct and inverse proportionality, challenges in applying mathematical principles, inability to represent concepts visually and symbolically, and difficulties in evaluating and reflecting on problem-solving steps. Other contributing factors include monotonous exercise routines, insufficiently supportive online learning, and students’ sensitivity to the context of word problems. Recommended instructional strategies include targeted remedial programs, the use of interactive media such as GeoGebra, the development of POE-based Learning Activity Sheets LKPD, Discovery Learning approaches, and exercises that promote critical reasoning. These findings are expected to serve as a reference for teachers and policymakers in designing more effective mathematics instruction.